Perbandingan Efektifitas Metode Quantum Learning dan Teaching Dengan Metode Konvensional Dalam Peningkatan Kapabilitas Belajar Mahasiswa: A Comparative Study on the Effectiveness of Quantum Learning and Teaching Method versus Conventional Method in Enhancing Students' Learning Capabilities - Mundir Mundir (Fenomena, 2002)
The passive learning outcomes and low examination scores in Islamic History courses suggest a fundamental pedagogical failure, potentially rooted in behaviourist-based conventional teaching. Grounded in constructivist theory, this study aims to compare the effectiveness of Quantum Learning & Teaching (QLT) with conventional methods, examine the role of student interest in learning, and test for interaction effects. A 2x2 factorial pretest-posttest control group experimental design was employed, with 48 university students randomly assigned to groups based on method (QLT vs. conventional) and interest level (high vs. low). Data were analysed using two-way ANOVA. The findings reveal that QLT produced significantly higher learning outcomes than conventional methods, students with high interest outperformed those with low interest, and, crucially, a significant interaction effect confirmed that the effectiveness of QLT depends on student interest. The study concludes that QLT is superior overall, but it is most impactful for highly interested students. It is recommended that educators adopt QLT principles while specifically designing motivational strategies to actively engage low-interest learners. Rendahnya nilai ujian dan sikap pasif mahasiswa pada mata kuliah Sejarah Peradaban Islam mengindikasikan adanya kegagalan pedagogis yang berakar pada metode konvensional beraliran behavioristik. Berlandaskan teori konstruktivistik, penelitian ini bertujuan untuk membandingkan efektivitas metode Quantum Learning & Teaching (QLT) dengan metode konvensional, menguji pengaruh minat belajar, serta menganalisis interaksi kedua variabel tersebut. Penelitian menggunakan desain eksperimental faktorial 2x2 dengan pretest-posttest kontrol group pada 48 mahasiswa, yang dianalisis menggunakan ANOVA dua jalur. Hasil penelitian membuktikan bahwa metode QLT menghasilkan kapabilitas belajar yang secara signifikan lebih tinggi daripada metode konvensional, mahasiswa dengan minat tinggi memperoleh hasil lebih baik daripada yang berminat rendah, dan terdapat efek interaksi yang signifikan. Kesimpulannya, metode QLT terbukti lebih efektif secara umum, namun efektivitasnya sangat bergantung pada tingginya minat mahasiswa. Rekomendasi penelitian ini adalah pendidik perlu mengadopsi prinsip QLT sekaligus merancang strategi khusus untuk meningkatkan keterlibatan mahasiswa yang memiliki minat rendah.